Epithelial‐mesenchymal transitions in bronchopulmonary dysplasia of newborn rats. Issue 11 (11th April 2014) - Yang, Haiping; Fu, Jianhua; Xue, Xindong; Yao, Li; Qiao, Lin; Hou, Ana; Jin, Linlin; Xing, Yujiao
Summary Background Bronchopulmonary dysplasia (BPD) is a major threat to the health of premature infants yet its pathogenesis is not fully understood. Epithelial‐mesenchymal transition (EMT) of lung epithelial cells may lead to BPD. Objective To investigate the potential occurrence of EMT in a newborn rat model of BPD. Methods Newborn rats were exposed to a hyperoxic environment within 12 hr of birth. Lung tissue and isolated alveolar epithelial type II cells (AT2 cells) were collected on Days 1, 3, 7, 14, and 21 after hyperoxic exposure. Pathological changes in lung tissue, alveolar development, ultrastructural changes in AT2 cells, co‐expression of surfactant associated surfactant protein C (SPC), and α‐smooth muscle actin (α‐SMA) were investigated. The relative expression of SPC, α‐SMA, E‐cadherin, and N‐cadherin were investigated in lung tissue and isolated AT2 cells. Results In lung tissue, alveolar development was attenuated from Day 7 onwards in the BPD model group; co‐expression of SPC and α‐SMA and ultrastructural changes typical of EMT were observed in AT2 cells from rats in the BPD group. SPC and α‐SMA expression levels were higher in tissue samples from the BPD group than in control samples. Beginning on Day 7, evidence of a switch from E‐cadherin to N‐cadherin expression was observed in BPD lung tissue sample and in isolated AT2 cells. Conclusion EMT of AT2 cells occurred in the hyperoxia‐induced newborn rat BPD model and resulted in attenuated alveolar development as a portion of the myofibroblasts accumulated in the lung originated from AT2 cells via EMT. Pediatr Pulmonol. 2014; 49:1112–1123. © 2014 Wiley Periodicals, Inc.